39th International Conference on Organizational Science Development: Organizations at Innovation and Digital Transformation Roundabout: Conference Proceedings - Marina Bajić; Šprajc, Polona; Podbregar, Iztok; Maletič, Damjan; Tomić, Daniel; Ziegler, Yvonne; Uli, Vincenzo; Arsenijević, Olja (2020)
The forthcoming 39th International Conference on the Development of Organizational Sciences adopts the development timeline to direct the ideas of the academic and professional public to ensure our better tomorrow. Changing the image of today’s individual, society, organizations and environment requires changes in the traditional performance structures from different perspectives. Is it enough to be innovative? Is it enough to direct the action through the prism of digital technology? Organizations are at the roundabout of the intersection of human innovation, process development and information technology with technological advances, where organizations are fostering competitiveness and creating an ecosystem of digital users. In the perception of modern organizations, the roundabout enables us to streamline digital transformation experiences, ideas and guidelines in a relatively short time, while reducing the time of uncertain decisions. Changing established business models coupled with the development of ideas, the promotion of innovation and technology, promotes change management towards an increasing synergy of innovation and digital transformation. The International Conference on the Development of Organizational Sciences traditionally encourages and in recent years increasingly integrates academic knowledge with professional solutions of economy and non-economy.
Keywords: innovation; organizational sciences; digital transformation; organizations; digitalization; international conference